2021
DOI: 10.1159/000512647
|View full text |Cite
|
Sign up to set email alerts
|

Duchenne and Becker Muscular Dystrophies’ Prevalence in MD STAR<b><i>net</i></b> Surveillance Sites: An Examination of Racial and Ethnic Differences

Abstract: <b><i>Introduction:</i></b> Previous studies indicated variability in the prevalence of Duchenne and Becker muscular dystrophies (DBMD) by racial/ethnic groups. The Centers for Disease Control and Prevention’s (CDC) Muscular Dystrophy Surveillance, Tracking, and Research network (MD STAR<i>net</i>) conducts muscular dystrophy surveillance in multiple geographic areas of the USA and continues to enroll new cases. This provides an opportunity to continue investigating differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
(33 reference statements)
1
7
0
Order By: Relevance
“…The observation that non-Hispanic blacks and Hispanics had a lower participation rate than non-Hispanic whites is consistent with observations in other diseases [27]. We note that although it was observed that non-Hispanic blacks have a lower prevalence of DMD than non-Hispanic whites [21,24], in this study we determined the rate of participation among identified patients, so the findings cannot be explained by this diagnostic discrepancy. Many explanations were proposed for discrepancies in trial participation by race or ethnicity [26,27].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The observation that non-Hispanic blacks and Hispanics had a lower participation rate than non-Hispanic whites is consistent with observations in other diseases [27]. We note that although it was observed that non-Hispanic blacks have a lower prevalence of DMD than non-Hispanic whites [21,24], in this study we determined the rate of participation among identified patients, so the findings cannot be explained by this diagnostic discrepancy. Many explanations were proposed for discrepancies in trial participation by race or ethnicity [26,27].…”
Section: Discussionsupporting
confidence: 88%
“…MD STARnet is a population-based public health surveillance program of nine muscular dystrophies, including dystrophinopathies, funded by the Centers for Disease Control and Prevention. Details about MD STARnet were published previously [19][20][21][22][23][24]. For this study, retrospective active surveillance data were collected by six sites: Colorado (CO), Iowa (IA), North Carolina, Piedmont region (NC), South Carolina (SC), Utah (UT), and New York's 21 western counties (wNY).…”
Section: Methodsmentioning
confidence: 99%
“…Another possible explanation for the delay in initial evaluation among non-Hispanic black males could be differences in gene frequency or gene expression. DMD prevalence has been shown to vary across racial/ethnic groups in the USA [20, 22]. Further, there are genetic modifiers known to modulate the DMD phenotype [37, 38], and there may be others still undiscovered.…”
Section: Discussionmentioning
confidence: 99%
“…MD STAR ne t is a multisite population-based surveillance system funded by the Centers for Disease Control and Prevention that identifies and follows individuals diagnosed with DBMD. The surveillance methodology has been described previously [18-22]. Briefly, data collection was initiated in 2004 at 4 sites (Arizona [AZ], Colorado [CO], Iowa [IA], and 12 counties in Western New York [wNY]); two additional sites were added in 2006 (Georgia [GA], Hawaii [HI]).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation